2018
DOI: 10.1002/ccr3.1980
|View full text |Cite
|
Sign up to set email alerts
|

Extracranial metastases in glioblastoma—Two case stories

Abstract: Key Clinical Message The clinician should always consider extracranial metastases in glioblastoma. Increased risk factors are young age at diagnosis, histology of gliosarcoma, and prior intracranial tumor surgery. Clinical guidelines are needed for this rare event, including consideration for prophylactic intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
5
0
2
Order By: Relevance
“…Historically, one of the major concern of shunt implantation in glioblastoma patients is the risk of peritoneal metastasis (32,(38)(39)(40)(41). However, it is now well established that spread by shunts is a rare albeit potential serious complication in highgrade gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, one of the major concern of shunt implantation in glioblastoma patients is the risk of peritoneal metastasis (32,(38)(39)(40)(41). However, it is now well established that spread by shunts is a rare albeit potential serious complication in highgrade gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…As such, scalp metastasis is usually located close to the surgical incision site, and this suggested that direct tumor seeding is a possible mechanism (12). To our knowledge, less than 20 cases of scalp metastases from GBM cells seeding were described (3,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). We summarize GBM patients with scalp involvement to further explore the characteristics of scalp metastasis (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, leptomeningeal spread is rare, occurring in 2-4% of GBM patients. Most patients are young and male and have undergone prior surgery, which is believed to allow cancer cells to access the extracerebral blood and lymphatic vessels [4]. Few case reports have been previously reported in which a single tissue or organ metastasis was present.…”
Section: Introductionmentioning
confidence: 99%